Pelatihan dan pendampingan pengelolaan keuangan berbasis teknologi pada BUMDes Duyung - Endang Mardianti; Yuki Firmanto (Unri Conference Series: Community Engagement, 2022)
In 2022, one of the government's programs and policies focus on advancing and developing the village economy. This is proved by the large amount of government budget allocated to village funds. One of the priorities for using village funds is for village economic recovery. That authority can be done by BUMDes (Village-Owned Enterprise) as the manager of village-owned business.Currently, BUMDes are intensively building infrastructure, improving and promoting natural and man-made tourism in their village, which Duyung Village-Owned Enterprise is part of it. All tourism places in Duyung Village have been already operated. The FEB UB community service team in accordance with their majority, in the financial sector, begin to explore the financial management of the BUMDes.After examination, BUMDes need arrangement of financial management, because so far BUMDes has only made simple financial reports. Moreover, BUMDes funds are currently increasing, both from village funds and from tourism operational income. The Service Team uses the community development method in community service at Duyung Village-Owned Enterprises. This method has five stages, namely engagement, assessment, planning, implementation, and evaluation. The result of this service is that financial management has been arranged and there are financial reports that are accountable by using cloud system technology